Pengaruh Return On Equity (ROE), Earning Per Share (EPS), Debt to Equity Ratio (DER), dan Price to Book Value (PBV) terhadap Return Saham dengan Kebijakan Dividen sebagai Variabel Mediasi: (Survey pada Perusahaan Indeks LQ45 yang terdaftar di Bursa Efek Indonesia Periode 2018 - 2022) - Isnan Taufikkurrohman; Ade Komaludin; Edy Suroso (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to test the direct and indirect effect of ROE, EPS, DER, and PBV on stock returns through dividend policy as a intervening variable. The research was conducted on LQ45 index companies listed on the IDX in the 2018 - 2022 period. The samples collected were 20 companies from 45 companies using the purposive sampling method. The data analysis technique was carried out using panel data regression assisted by the Eviews 12 application. The research results show 1) ROE and EPS have a significant negative effect on Dividend Policy, 2) DER has an insignificant negative effect on Dividend Policy, 3) PBV has a positive and significant effect on Dividend Policy, 4) ROE and DER have an insignificant positive effect on Stock Returns, 5) EPS has an insignificant negative effect on Stock Returns, 6) PBV has a significant negative effect on Stock Returns, 7) Dividend Policy is able mediates the influence of ROE perfectly (complete mediation) and the influence of PBV partially (partial mediation) on Stock Returns, 7) Dividend Policy is unable to mediate the influence of EPS and DER on Stock Returns.